PEMBELAJARAN ONLINE MENGHADAPI WABAH COVID 19 - Betri, Tigus Juni (UNIVERSITAS SLAMET RIYADI, 2020)
Online learning information that leads to an era of both digital processes and content in the era of the industrial revolution 4.0 is needed to keep up with the rapid development of the world of education. Learning activities can occur anywhere and anytime with online learning. The Covid 19 epidemic appears to hit the world at the end of 2019 and has stepped into total preparation. Need a high vigilance because of limited direct contact interaction with other humans. This has an impact on the continuity of learning in schools, so learning activities must be adapted into online forms. This article discusses an overview of online learning in dealing with the Covid-19 outbreak. The results of the study suggest that preparatory steps are needed as well as clear stages in online learning activities. In addition, the flexibility and adaptability of teachers and students plays an important role in online learning activities.Keywords : Covid-19, E-Learning, Industrial Revolution 4.0, Online , PandemicÂ Pembelajaran online informasi yang mengarah pada era digital baik proses maupun konten di era revolusi industri 4.0 sangat dibutuhkan untuk mengikuti perkembangan dunia pendidikan yang begitu pesat. Kegiatan pembelajaran dapat terjadi dimana saja dan kapan saja secara fleksibel dengan pembelajaran online. Wabah Covid 19 muncul menghempaskan dunia di akhir tahun 2019 dan memaksa segalanya beradaptasi total. Perlu sebuah kewaspadaan tinggi karena terbatasnya interaksi kontak langsung dengan manusia lain. Ini berdampak pada kelangsungan pembelajaran di sekolah, sehingga kegiatan pembelajaran harus diadaptasi ke dalam bentuk online. Artikel ini membahas tinjauan pembelajaran online dalamÂ menghadapi wabah covid-19. Hasil penelitian mengemukakan bahwa diperlukan langkah langkah persiapan serta tahapan jelas dalam kegiatan pembelajaran online. Selain itu fleksibilitas dan kemampuan adaptasi guru dan siswa berperan penting dalam kegiatan pembelajaran online.Kata Kunci : Covid-19, Online, Pandemi, Pembelajaran Elektronik , Revolusi Industri 4.0Â